1987
DOI: 10.1002/jcp.1041320120
|View full text |Cite
|
Sign up to set email alerts
|

Suramin inhibition of growth factor receptor binding and mitogenicity in AKR‐2B cells

Abstract: Suramin, a polyanionic compound, has previously been shown to dissociate platelet-derived growth factor (PDGF) from its receptor. In the present study suramin was found to inhibit the growth of sparse cultures of AKR-2B cells in fetal bovine serum (FBS)-supplemented medium in a dose-dependent, reversible fashion. Suramin also inhibited the ability of FBS, transforming growth factor beta (TGF beta), heparin-binding growth factor type-2 (HBGF-2), and epidermal growth factor (EGF) to stimulate DNA synthesis in de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
147
0
1

Year Published

1995
1995
2003
2003

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 356 publications
(155 citation statements)
references
References 25 publications
7
147
0
1
Order By: Relevance
“…It is important to realize that suramin "normalizes" the phenotype of some tumor cell lines (25,26,43). Work now in progress is focused on determining the effect of suramin on the phenotype of tumor cells in an effort to understand whether lysyl oxidase mediates normalization of the cell phenotype by suramin, perhaps by somehow regulating phosphatidylinositol 3-kinase localization and activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to realize that suramin "normalizes" the phenotype of some tumor cell lines (25,26,43). Work now in progress is focused on determining the effect of suramin on the phenotype of tumor cells in an effort to understand whether lysyl oxidase mediates normalization of the cell phenotype by suramin, perhaps by somehow regulating phosphatidylinositol 3-kinase localization and activity.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, suramin is active against human immunodeficiency virus-1 (40). Suramin inhibits the binding of growth factors to their respective receptors, and this mechanism is believed to primarily contribute to its therapeutic effects (24,34,(41)(42)(43).…”
mentioning
confidence: 99%
“…It inhibits the activities of several heparin-binding growth factors such as transforming growth factor-beta, fibroblast growth factor and platelet-derived growth factor (Coffey et al, 1987;Kopp & Pfeiffer, 1990;Myers et al, 1990). In a rat brain tumour model, suramin inhibits endothelial and tumour cell proliferation (Takano et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…In spite of major toxicities, suramin has been documented to have significant in vitro and in vivo activity against a variety of solid tumor cell lines at drug concentrations that are clinically achievable (Betscholtz et al, 1986;Coffey et al, 1987;Kim et al, 1991;Gansler et al, 1992). For this reason, there continues to be considerable clinical interest in this drug.…”
Section: Introductionmentioning
confidence: 99%
“…However, the mechanism of anti-tumor activity and neurotoxicity of the drug remain unknown. Most reports on suramin describe an inhibitory effect on growth factor receptor binding as its cytotoxic mechanism of action (Hosang, 1985;Coffey et al, 1987;Sjo È lund and Thyberg, 1989;Pollack and Richard, 1990). Other studies have reported a stimulatory effect by suramin on growth factor receptors (Mahoney et al, 1990;Cardinali et al, 1992;Sartor et al, 1992;Tsutsumi et al, 1993;Tsutsumi et al, 1994).…”
Section: Introductionmentioning
confidence: 99%